Civics Education Learning and Discipline Character of Fifth-Grade Elementary School Students: A Correlational Study - Fintje Oppier; Samuel P. Ritiauw; Lisye Salamor (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Discipline character is a cornerstone of Indonesia’s national character education policy, yet empirical evidence linking Civics Education (Pendidikan Pancasila dan Kewarganegaraan/PPKn) to disciplinary outcomes in elementary schools remains scarce. This study examined the relationship between PPKn learning and fifth-grade students' discipline character at Elementary School Eri, Indonesia, during the 2024/2025 academic year, quantifying its specific contribution. Utilizing a quantitative correlational design, a total sampling approach was applied to the entire population of 21 fifth-grade students. Data were gathered through validated four-point Likert-scale questionnaires measuring perceived PPKn quality and disciplinary behavior and subsequently analyzed using descriptive statistics and Pearson product-moment correlation. Results indicated that both PPKn learning (M = 81.43, SD = 7.41) and discipline character (M = 83.29, SD = 3.66) were categorized as high. A moderate, positive correlation was observed (r = 0.4229); however, the r-count value fell marginally below the critical r-table threshold (0.433) at α = 0.05, retaining the null hypothesis. The coefficient of determination (R2) revealed that PPKn learning accounts for 17.88% of the variance in discipline character. Although statistically non-significant, the moderate association demonstrates that civics education provides a meaningful, albeit partial, contribution to character formation. The remaining variance points to external factors like family and peers, underscoring the need for ecosystem-based character education strategies and larger-scale replication studies.